Alkaloid production by Claviceps sp. SD-58; involvement of phosphatase isozymes - Vaidya, H C; Desai, J D (Folia microbiologica, 1983)
Simultaneous reduction in alkaloid yield and level of phosphatases by high concentrations of phosphate was observed in Claviceps sp. SD-58. Tryptophan-induced culture showed an increase in alkaloid yield and the level of phosphatases. Phosphate caused repression of both acid phosphatase (isoenzyme I) and alkaline phosphatase (isoenzymes III and V).
Keywords: tryptofan; izoenzymy; Potassium; Culture Media; draslík; kultivační média; Alkaloids; Potassium Compounds; sloučeniny draslíku; Alkaline Phosphatase; alkalická fosfatasa; Claviceps; Tryptophan; kinetika; Phosphates; Acid Phosphatase; fosfáty; Isoenzymes; Kinetics; alkaloidy; kyselá fosfatasa